Innovative Biological Solutions to Challenges in Sustainable Biofuels Production - Yang, Xiaohan; Li, Ting; Weston, David; Karve, Abhijit; Labbe, Jessy L.; Gunter, Lee E.; Sukumar, Poornima; Borland, Anne; Chen, Jin-Gui; Wullschleger, Stan D.; Tschaplinski, Timothy J.; Tuskan, Gerald A. (IntechOpen, 2011)
None